LOVE CONFLICT BETWEEN TWO MAIN CHARACTERS IN SENSE AND SENSIBILITY: A Feminism Perspective on the Novel Written by Jane Austen - Yuanita Puspita, - (2007)
This research, entitled Love Conflicts Between Two Main Characters In Sense and Sensibility, aims to investigate the love conflict between two main characters from feminism perspectives in the novel by Jane Austen, entitled Sense and Sensibility. Using qualitative content analysis methods the research answers the following questions: ( 1) what love conflicts are faced by the two main characters in the novel and (2) how are the love conflicts viewed from feminism perspectives. The samples of the research are 27 issues selected out of 50 chapters from the novel. The research finds that the two female characters in the novel have their own love conflicts which are caused by difference in social status, gender roles and points of view to express the meaning of love and different culture with male characters in their journey to find a better life.